Study on the bacteriostasis of lemon essential oil and the application of lemon essential oil nanoemulsion on fresh-cut kiwifruit - Chen, Chuan; Meng, Fan-Bing; Lv, Han-Jia; Gou, Zhen-Zhen; Qiu, Jing; Li, Yun-Cheng (Frontiers in Sustainable Food Systems, 2024)
Fresh-cut fruit has been popularized for use by consumers in recent years, but its shelf life is very short. Plant essential oils have received attention for their bioactive properties, such as antibacterial and antioxidant properties, but their volatile nature limited their application in foods. In this study, the bacteriostasis of lemon essential oil (LEO) was verified, and LEO nanoemulsion was prepared to preserve fresh-cut kiwifruit. Compared with those of gram-negative bacteria, the inhibition zone diameters of LEO against gram-positive bacteria were significantly greater, measuring 12.20 ± 0.67 mm (Staphylococcus aureus) and 14.23 ± 0.61 mm (Listeria monocytogenes), compared to 9.50 ± 1.08 mm (Escherichia coli). At a concentration of 50 mg/mL, LEO exhibited DPPH and ABTS radical scavenging rates of 84.88 and 83.01%, respectively, which were comparable to those of 10 mg/L vitamin C (VC). Konjac glucomannan, whey protein and LEO were used to prepare nanoemulsion. When 2.0% LEO was added, the nanoemulsion exhibited great stability, which resulted in a decrease in particle size to 220.80 nm, a decrease in PDI to 0.238, and an increase in zeta potential to-27.83 mV. The stability of the nanoemulsion with added LEO was superior to that of the nanoemulsion without LEO on the 15th day. Preservation tests on fresh-cut kiwifruit demonstrated that, on the 8th day, compared with no treatment, nanoemulsion containing 2.0% LEO reduced the weight loss rate from 3.20 to 1.16%, increased the firmness from 20.459 to 38.23, and decreased the decay rate from 80.69 to 41.74% compared to untreated kiwifruit. It also effectively maintained the original color of fresh-cut kiwifruit and had positive effects on the soluble solid content, titratable acid content, VC content, and total colony count. LEO has great bacteriostatic and antioxidant activity, and the use of LEO nanoemulsions on fresh-cut kiwifruit can effectively maintain various indicators of fresh kiwifruit after a 8-day storage period.